The role of glucagon in weight loss‐mediated metabolic improvement: a systematic review and meta‐analysis. (16th November 2017) - Silvestre, M. P.; Goode, J. P.; Vlaskovsky, P.; McMahon, C.; Tay, A.; Poppitt, S. D.
Summary: Aims This meta‐analysis aimed to investigate the role of glucagon suppression in regulating glucose homeostasis following diet or bariatric surgery. Methods A comprehensive search of intervention and observational studies was conducted in Medline, Scopus, Web of Science, PubMed and Embase. Random effects model meta‐analysis was performed. Primary outcomes were (i) body weight change, (ii) fasting glucagon, (iii) fasting glucose and (iv) fasting insulin concentrations. Results Twenty articles reporting data from 29 interventions were eligible for analysis. Bariatric surgery caused greater weight loss than diet (bariatric −29.7 kg [CI:‐36.8, −22.6]; diet −5.8 kg [CI: −8.4, −3.3]; P < 0.00001), an effect that remained significant after adjusting for study duration ( P < 0.05). Mean fasting glucagon decreased in parallel with weight loss (−11.8 ng/L [CI: −15.9, −7.8]; P < 0.00001) with no difference between bariatric and diet intervention. Both fasting glucose, and insulin decreased following weight loss (both P < 0.00001; glucose −1.7 mmol/L [CI: −2.0, −1.3]; insulin −50.6 pmol/L [CI: −66.5, −34.7] with greater decrease in fasting insulin between bariatric versus diet ( P = 0.01). Conclusions Synergistic suppression of fasting glucagon and insulin resistance may act together to restore normoglycaemia following weight loss. Whether suppression of plasma glucagon may contribute to increased hunger after weight loss and gradual weight regain is not yet known.